2014
DOI: 10.1021/jp410059e
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Size-Selected Copper Cluster Cations and Anions with Nitric Oxide: Enhancement of Adsorption in Coadsorption with Oxygen

Abstract: Reactions of size-selected Cu(n)(±) and Cu(n)O(m)(±) (n = 3-19, m ≤ 9) clusters with NO were investigated in the near-thermal energy region under single collision conditions using a tandem-type mass spectrometer with two ion-guided cells. Oxygen atoms preadsorbed on the cluster can significantly enhance the NO adsorption probability and cause additional reactions. NO adsorption is observed particularly for anionic copper cluster dioxides, Cu(n)O2(-) (n ≥ 8), followed by the release of a Cu atom from Cu(n)O2(-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 45 publications
4
64
0
Order By: Relevance
“…Two product species, Cu 8 O 2 NO − and Cu 7 O 2 NO − , appear dominantly as described in our recent study. 13 Additionally, another peak is also observed at m/z ≈ 445, very slightly in Figure 1a and clearly in Figure 1b Figure 2). Furthermore, this assignment is supported by comparing the mass spectrum in Figure 1b with that measured in the CID experiment of Cu 8 O 2 − by Xe ( Figure 1c) because the intensity of the m/z = 445 peak in the multiple collision reactions with NO is considerably higher than that of Cu 7 − in Cu 8 O 2 − + Xe.…”
Section: Figure 1 (Panels a And B) Shows Typical Mass Spectra Obtainementioning
confidence: 80%
See 3 more Smart Citations
“…Two product species, Cu 8 O 2 NO − and Cu 7 O 2 NO − , appear dominantly as described in our recent study. 13 Additionally, another peak is also observed at m/z ≈ 445, very slightly in Figure 1a and clearly in Figure 1b Figure 2). Furthermore, this assignment is supported by comparing the mass spectrum in Figure 1b with that measured in the CID experiment of Cu 8 O 2 − by Xe ( Figure 1c) because the intensity of the m/z = 445 peak in the multiple collision reactions with NO is considerably higher than that of Cu 7 − in Cu 8 O 2 − + Xe.…”
Section: Figure 1 (Panels a And B) Shows Typical Mass Spectra Obtainementioning
confidence: 80%
“…13 We found that the NO adsorption probabilities of copper cluster anions are dramatically enhanced by the preadsorption of two oxygen atoms in the size range of n ≥ 8. Furthermore, we observed that NO adsorption onto Cu n O 2 − (n = 8, 10, and 12) is followed by the release of a Cu atom.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…23 Recently, we revealed that the preadsorption of seemingly harmful oxygen atoms onto copper cluster anions enhances the adsorption probability of NO and promotes the decomposition of NO. 22,24 This could be attributable to the contribution of 3d orbitals of the copper atoms. It is thus expected that the doping of p-or d-block metals such as aluminum or transition metals also affect the cluster reactivity drastically.…”
Section: Introductionmentioning
confidence: 99%